BSAC Vanguard Series: AMR diagnostics in light of evolving technologies and access in low- and middle-income countries. (17th November 2021) - Berman, Daniel; Neale, Ruth
Abstract: Rapid point-of-care tests are needed to control antimicrobial consumption, as recognized by the Longitude Prize. However, in addition to bacterial pathogen identification, clinicians need more information, such as which antimicrobial will be effective and how severe the infection really is. This technology is beginning to emerge, but both economic and technological challenges remain before it can be delivered, especially in low- and middle-income countries. This article outlines these challenges and how we might overcome them.